A Sociolinguistic Experiment in Defining the Forms of Impoliteness - Svitlana Formanova; Tetiana Dombrovan (Психолінгвістика, 2019)
The importance of the study is determined by the need for a comprehensive analysis of the conducted sociolinguistic experiment in order to identify the forms and means of impoliteness and to clarify the linguistic status of the latter. The objective of the article is, by means of a survey, to find out the forms, types and means of impoliteness among the student youth. The investigation of social awareness of the anti-etiquette space based on the analysis of the SE participants’ answers has never before been in the focus of linguists. The object of the study is the sociolinguistic experiment, the subject being the characteristics of forms and means of impoliteness. The following scientific methods are employed: the method of observation – to fix linguistic and non-linguistic expressions of anti-etiquette forms; the descriptive method – to identify the characteristic features of forms and means of impoliteness; analysis and synthesis of factual material in order to systematize and classify the factual material; the field research method with a questionnaire as its most common technique – to collect the corpus; the quantitative method and the method of sociolinguistic analysis of the collected corpus – to process the revealed facts about the subject of the study; the psycholinguistic method – to process and analyze the speech data received from informants as a result of questioning, which helped to establish the forms, types and methods of impoliteness among students. Findings. The authors claim that a high degree of impoliteness in the speech of young people is a means of self-expression and self-establishment, a striving for violation of social taboo, a way to set up one’s own communicative rules. The use of the anti-etiquette forms of communication is influenced by a variety of factors such as age, sex, social status, area of residence, education, and profession. The survey has revealed certain differences in the regional use of the anti-etiquette forms in Ukraine. Being accurate and emotionally colored, those forms express a negative phenomenon which sometimes exists in the process of communication.